The Potency of Obtained Clean Water from Rainwater Harvesting in Sikka District - Mbarep, Daniel Putra Pardamean; Apelabi, Gabriel Otan; Bolly, Yovita Yasintha; Nurhidayat, Agus (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Sikka District is one of the areas experiencing a clean water crisis because only 5.23 % of people have access to clean water in 2020. Therefore, rainwater management will be carried out to obtain clean water using roof top rainwater harvesting technology. This study aims to calculate the potency of clean water that can be obtained from rainwater harvesting. Comparative descriptive analysis method was used to compare the data of clean water potency that can be obtained from rainwater harvesting with the data of clean water needs from the people in Sikka District in 2020. The results show that the potency of clean water that can be obtained from rainwater harvesting is 3,593961.6 m3/year or 3,593,961,600 liters/year and clean water needs of all the people is 17,626,927 m3/year or 17,626,927,000 liters/year. The people that gets clean water from rainwater harvesting is 20.38 % or as many as 65,615 people from the total population in Sikka District. This shows that the use of rainwater cannot meet the clean water needs of all people in Sikka Distric. There is a need for other sources of clean water that are bigger and can be used to meet the needs of all people.